Neither passivity nor resistance: Competitive ways of building citizenship from the neighborhood leadership - Luján, David (2019)
This essay tries to answer the following questions: how and under what conditions do social actors become citizens? And how does the principle of citizenship work among different groups? Through a qualitative and ethnographic methodology focused on the stories of sixty neighborhood leaders in a Chilean commune, we propose 1) citizenship as a series of links between society and the State, in which meanings are daily constructed around social inclusion and exclusion, which are brought into play in face-to-face contacts through differentially distributed resources, skills and capacities; 2) sociopolitical ties beyond the absolute distinction between clientelist and contestatory actors to analyze their similarities and differences.